The 2024 generation - Aggarwal, Shruthy Suresh; Andreani, Cristina; Deng, Zihou; Frede, Julia; Kameneva, Polina; Kovatcheva, Marta; Micevic, Goran; Nicolson, Fay; Puschhof, Jens; Roberts, Morgan; Wang, Gang; Watson, Dionysios C. (Nature cancer, 2024)
Twelve early-career researchers who embarked on their independent research paths in 2024 reflect on their experience from their journey so far, describe the opportunities they received and the challenges they faced, and share their hopes and plans for the future.
Gesehen am 03.04.2025